Avaliação temporal de comportamentos de risco e percepção de vulnerabilidade para DST/AIDS em mulheres na cidade de Pelotas: 1999-2012 - Mesenburg, Marilia Arndt (2012)
Background: sexually transmitted diseases are an important public health problem worldwide, and the sexual behavior is a key factor for the susceptibility of these diseases. An evaluation of the sexual behavior of women in reproductive age was conducted in 1999. A replication of this study aims to evaluate the current situation and identify changes in the sexual behavior, after 13 years. Methods: it is a population-based cross-sectional study with a multistage sampling, conducted in a city in southern Brazil. Through a confidential self-applied questionnaire , we investigated the sexual behavior of 1071 women. Results: compared to the 1999 study it was observed in 2012 an increase of 14 percentage points in early sexual debut and a decrease of 8 percentage points in the non-use of condoms. The proportion of women who reported anal sex has doubled between the periods. There were no significant differences in the proportion of women reporting alcohol and drug use both by themselves and by their partners and multiple sexual partners, and there was no change in the perception of vulnerability. Conclusions: there was no trend of increase or decrease in the prevalence of the set of behaviors being observed distinct patterns for each of them. The decrease in the prevalence of non-use of condom use may be an indicator of the effectiveness of campaigns to promote safe sex. However, the increased prevalence of early sexual debut and anal sex indicates the need for campaigns to continue and to expand their focus, especially among high-risk groups.